(3CUhd JQcjH GdCOhjIs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdaGVd eMeO Hf Ydi GdSeQbfOi Ef GdhGLH Ydi cd Pi dH Cf jJbQH Edi Gddg hjJhSd Edjg hCMSf GdhSGFd hCLhO GdPQGHY EeJKGd GdChGeQ hGdfhGgi eGjYhO Ydi faY GdfGS YGeg s
(3BNQgG (B:s
(3hbO jLYd HOd GdYaU EPG de jQO Hg TOI GdShGO Je GdcJGH s
(3fSNI CNQi ef GdbSe GdKGdK ef GdfLjHGJs
(3HChdgG agQS ddehVhYGJ ddYdGeI CMeO JjehQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
(3agQS GdWH (B- (3U (B195 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B270 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs